ANALISIS DATA ANTREAN DALAM LAYANAN RESTORAN CEPAT SAJI MENGGUNAKAN LINEAR REGRESSION - Manurung, Nadia; Arianto, Dede Brahma (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Queuing is a situation of waiting for your turn to be served. Long queues are caused by the number of consumers coming more than the number of service facilities. This research was carried out at the MC Donald fast food restaurant during lunch time. The aim of the research is to analyze the relationship between queue times in fast food restaurant services and the factors that influence it. Linear Regression modeling is used to model and predict queue times based on variables of number of customers and length of service time. Based on the simulation results, the Mean Absolute Error (MAE) value was 1.23 and the Mean Squared Error (MSE) was 2.16.